2008
DOI: 10.1007/s00213-008-1177-9
|View full text |Cite
|
Sign up to set email alerts
|

S32006, a novel 5-HT2C receptor antagonist displaying broad-based antidepressant and anxiolytic properties in rodent models

Abstract: S32006 is a potent 5-HT(2C) receptor antagonist, and possesses antidepressant and anxiolytic properties in diverse rodent models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 110 publications
(98 citation statements)
references
References 115 publications
2
93
3
Order By: Relevance
“…These results further suggest that this regional stimulatory effect of agomelatine on cell proliferation is not mediated by melatonin receptors, but rather by the blockade of 5-HT 2C receptors. Indeed, two different 5-HT 2C receptor antagonists, SB243,213 and S32006 (Wood et al, 2001;Dekeyne et al, 2008), mimicked agomelatine's effect on cell proliferation in the VH only. In line with these observations, it has also been demonstrated that 5-HT 2C receptor-binding sites are more densely expressed in the VH compared with DH (Holmes et al, 1995).…”
Section: Adult Neurogenesis and Antidepressantmentioning
confidence: 98%
See 2 more Smart Citations
“…These results further suggest that this regional stimulatory effect of agomelatine on cell proliferation is not mediated by melatonin receptors, but rather by the blockade of 5-HT 2C receptors. Indeed, two different 5-HT 2C receptor antagonists, SB243,213 and S32006 (Wood et al, 2001;Dekeyne et al, 2008), mimicked agomelatine's effect on cell proliferation in the VH only. In line with these observations, it has also been demonstrated that 5-HT 2C receptor-binding sites are more densely expressed in the VH compared with DH (Holmes et al, 1995).…”
Section: Adult Neurogenesis and Antidepressantmentioning
confidence: 98%
“…All procedures were conducted in accordance with the French Agriculture and Forestry Ministry (decree 87848, license 01498). SB242,084, a selective 5-HT 2C receptor neutral antagonist (Kennett et al, 1997), SB243,213, a selective 5-HT 2C receptor inverse agonist (Wood et al, 2001), and S32006, a novel 5-HT 2C receptor inverse agonist (Dekeyne et al, 2008), were injected once a day, at 10 mg/kg i.p. dissolved in sterile water or 1% hydroxyethylcellulose (HEC).…”
Section: Animals and Drug Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…[85][86][87] In addition, blockade of ventrotegmental-and locus ceruleus-localized 5-HT 2C sites disinhibits dopaminergic and adrenergic pathways, respectively, and 5-HT 2C antagonists elicit robust antidepressant and anxiolytic actions in a broad range of paradigms. 40,85,86,88 -90 Blockade of 5-HT 2C sites may, further, enhance sexual function and improve restorative slow wave sleep, 42,85,91 and antagonism of hypothalamic 5-HT 2C receptors facilitatory to the hypothalamo-pituitary-adrenocortical (HPA) axis abrogates its overstimulation by stress.…”
Section: Bimodal Antidepressants Acting As 5-ht 2c or 5-ht 2a Receptomentioning
confidence: 99%
“…68,116 5-HT 1B receptors have also been forwarded as mediators of antidepressant actions of SSRIs, together with 5-HT 2A and (controversially) 5-HT 2C and 5-HT 6 sites; 5-HT 4 receptors were also recently added to the inventory of potential serotonergic mechanisms for improving mood. 3,58,86,[117][118][119] No single receptor can account for the global therapeutic influence of antidepressants that increase monoamine levels. For example, cellular substrates controlling neurogenesis in the hippocampus differ from those that counter anhedonia.…”
Section: Recruiting Subsets Of Postsynaptic Sites Mediating Beneficiamentioning
confidence: 99%